Proposta de uma sequência didática sobre óleos essenciais para o ensino de química na modalidade EJA - Bitencurt, Juliana Schmatz (2021)
The focus of this work is to build a didactic sequence using experimental activities ,with the theme “essential oils”, to verify the learning of the Chemistry content by students of the EJA (Youth and Adult Education) modality. The research was implemented with students from Totalidade 7, from a School in the municipality of Salto do Jacuí, RS-BR in the second semester of 2019, addressing Chemistry concepts. Didactic sequences were constructed with experimental activities to address contents such as matter, properties it has and transformations it undergoes. Through a Potentially Significant Teaching Unit - UEPS, activities were developed to value the student's prior knowledge by promoting knowledge in the classroom, for this, the contextualization of the content using a theme that refers to the senses, used in daily life, becomes an ally of pedagogical practices. The investigative analysis of the results was verified through questionnaires, experimental activities, individual tests and a diary containing the observations made by the teacher in a qualitative assessment. At the end of the application of the didactic sequence, the students appropriated concepts of Chemistry, previously unknown, applying it in their daily practices. The use of the essential oils theme in the involvement of applied theoretical and experimental activities had as a sign of significant learning. Through the results obtained in this research, we concluded that the teaching of Chemistry was favored both by the theme and by the methodology used, UEPS, thus obtaining more accessible ways of relating the studied contents to everyday life.